Evaluating Primary School Teacher Professional Development Programmes in Zimbabwe: Pre-Service Student Teacher’s Views - Mufanechiya, Albert; Kanyopa , Theresia Joakim; Mokhele-Makgalwa , Matseliso (Journal of Ecohumanism, 2024)
Teacher education conversation is a critical focus area given its distinctive contribution to nation building. The study explores pre-service student teachers’ perceptions of the college and university teacher preparation practices. One aspect that has remained contested, and with competing ideas in the teacher education discourse in Zimbabwe is the quality and effectiveness of the programmes by two teacher education institutions. In this phenomenological study, we conveniently sampled twenty pre-service primary teacher students, ten from each institution. The design allowed us to focus on what and how the pre-service students experienced the teacher development programmes at institutions and the sense they made of those experiences. Focus group discussions with two sets of student participants and complemented by non-participant observation were data collection instruments. The key finding of the study is that the pre-service student teachers believe that the current professional development programmes do not adequately address their needs and challenges due to gaps in curricula, theory and practice and institutional and government support systems. The study recommends the need to come up with one primary teacher professional development system that considers the strengths from each of the two models in existence. The study contributes to the broad discourses on teacher development in Zimbabwe highlighting the need to identify the programmes’ strengths, areas of improvement, and informed decisions on appropriate pre-service student teacher support, learning and professional growth.